Pengaruh Senam Direct Intruction Terhadap Pengembangan Motorik Kasar Anak Usia 5-6 Tahun di Tk Cerdas Ceria Tapian Nauli Kecamatan Sipoholon - Rosa Enjelina Silaban; Uranus Zamili; Emmi Silvia Herlina (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Silaban, Rosa. 2023. "The Effect of Direct Instruction Gymnastics on the Gross Motor Development of Children Aged 5-6 Years in the Smart Ceria Tapian Nauli Kindergarten, Sipoholon District". The aim of this research is to determine the effect of direct instruction gymnastics in the gross motor development of children aged 5-6 years at the Smart Ceria Tapian Nauli Kindergarten, Sipoholon sub-district. The method used in this research is a quantitative research method with a pre-experimental design type of research in the form of "One Shot Case Study". The population is all group B students (aged 5-6 years) at the Smart Ceria Tapian Nauli Kindergarten for the 2022/2023 academic year, totaling 42 children and a sample of 20 people was taken using a purposive sampling technique. Data was collected using a positive closed questionnaire with 20 items, namely 10 items for variable Ceria Tapian Nauli, Sipoholon District is known through: 1) Test of analysis requirements: a) positive relationship test obtained rxy = 0.687 > rtable(=0.05,n=20) = 0.444 thus it is known that there is a positive relationship between variable ) Regression coefficient of determination test (r2) = 47.2%. 2) Influence test: Regression equation test, obtained the regression equation Y ̂="17.24"+0.49X. Thus Ha is accepted and H0 is rejected. Keywords: Direct Instruction Gymnastics, Children's Gross Motor